India-Sri Lanka dialogue, 27-28 April 1995, New Delhi (RGICS proceedings, 1995)
Summary of a dialog between India and Sri Lanka on 27-28 April 1995 consisting of participants from different walks of life organized by Rajiv Gandhi Institute for Contemporary Studies.